INTEGRASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DAN HUKUM KELUARGA ISLAM DALAM MEMBANGUN KELUARGA SAKINAH - Amir Bandar Abdul Majid; Khoirun Niswatin (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
This paper critically examines the book Marriage Guidance for Prospective Brides and Grooms published by the Ministry of Religious Affairs of the Republic of Indonesia by highlighting the absence of integration of Islamic Religious Education (PAI) in the construction of family education. This study uses a qualitative-descriptive approach based on content analysis of the substance of the book's material. The results of the study indicate that the book emphasizes administrative, psychological, and reproductive health aspects, but does not yet present a systematic framework for family education based on PAI values. The concept of family education, both the relationship between husband and wife, wife and husband, and both towards children, is not formulated as a continuous pedagogical process. In fact, from an Islamic perspective, the family is the first madrasah (al-madrasah al-ūlā) for the formation of children's faith, worship, and morals. In addition, the book does not include procedures, stages, or strategies for resolving family conflicts that are structured as an effort to achieve a sakinah family. The absence of this normative-educational framework has implications for weak theological and pedagogical foundations in building a family oriented towards Islamic values. Therefore, it is necessary to reconstruct the guidance materials for prospective brides and grooms by integrating the Islamic Religious Education paradigm as the basis for family education. This ensures that the family is understood not only as a social institution but also as an educational institution for faith, morals, and civilization.